Atividade antifúngica do óleo essencial de Origanum vulgare Linneus (Orégano) sobre fungos oportunistas do gênero Fusarium - Viana, Waléria Pereira (2013)
Fusarium species have emerged as one of the more clinically important groups of filamentous fungi, causing localized and invasive infections with high morbidity and mortality in immunocompromised patients. Due to increasing clinical relevance of Fusarium and because the antimicrobial properties of essential oils have been known for many centuries this study aimed to evaluate the effectiveness of essential oils in inhibiting the growth of Fusarium solani and Fusarium oxysporum. In this study, the following methods have been used: microbiological screening; determination of minimum inhibitory concentration (MIC) and minimal fungicidal concentration (MFC); kinetics of microbial death; inhibition of coinidia germination and evaluation of morphological changes. The analysis of the oil chemical composition was performed by gas chromatography-mass scpectrometry (GC-MS). Among seven essential oils tested, Ocimum gratissimum Blume and Origanum vulgare L. essential oils exhibited potent antifungal activity, noted by the large growth inhibition zones with the average diameter of 29 and 42mm, respectively. The phytochemical analysis of O. vulgare showed that the main constituents of the essential oil are carvacrol (67,97 %), pcymene (11,67 %), -terpinene (7,92 %), thymol (7,84 %) and linalool (3,44 %). The essential oil from O. vulgare had a significant inhibitory effect on all assayed fungi. The values of MIC were 128 and 256 μg/mL, while MFC were in the range of 256 to values over 1.024 μg/mL, for the essential oil of O. vulgare. The essential oil from O. vulgare at 128, 256, 512 and 1.024 μg/mL strongly prevented mycelial growth. In these same concentrations, the oil was effective in inhibited the conidia germination of both species. Determination of the essential oil s effect over Fusarium strains morphogenesis demonstrated the essential oil was able to cause decreased conidiation, leakage of cytoplasm (empty hyphae) and distorted development hyphae. Given this, it is concluded that the essential oil from O. vulgare showed a strong inhibitory activity against Fusarium species and can be regarded as a potential product with antifungal properties, especially for the treatment of mycoses caused by Fusarium spp.